The 9th grade students' mathematical understanding in problem solving based on Pirie-Kieren theory. Issue 4 (February 2019) - Nopa, J R; Suryadi, D; Hasanah, A
Abstract: The purpose of this study is to analyse the mathematical understanding in 9th grade students' problem solving based on Pirie-Kieren theory. The Pirie-Kieren theory provides a framework to evaluate the students' mathematical understanding in solving mathematical problem. The layers of mathematical understanding in Pirie-Kieren theory consist at primitive knowing, image making, image having, property noticing, formalising, observing, structuring, and inventizing. This study designed according to case study toward two students who are studying at one of primary school in Bandung district. The participants in this study were selected among voluntary students by considering their mathematics interesting and recommendation from the mathematics teacher. The data was collected by testing and interviewing. One problem solving item was posed for the mathematics test. The interview of this study was collected by through a semi-structured interview. The obtain data was descriptive analysis with qualitative approach based on Pirie-Kieren theory. The result show that two of participant was started working at image having layer and they have placed at formalising layer. The participants have lacked at primitive knowing and image making according to Pirie-Kieren theory.